Effects of Bacterial Nanocellulose Loaded with Curcumin and Its Degradation Products on Human Dermal Fibroblasts - Zikmundova, Marketa; Vereshaka, Maria; Kolarova, Katerina; Pajorova, Julia; Svorcik, Vaclav; Bacakova, Lucie (Materials (Basel, Switzerland), 2020)
Bacterial nanocellulose has found applications in tissue engineering, in skin tissue repair, and in wound healing. Its large surface area enables the adsorption of various substances. Bacterial nanocellulose with adsorbed substances can serve as a substrate for drug-delivery of specific bioactive healing agents into wounds. In this study, we loaded a bacterial nanocellulose hydrogel with curcumin, i.e., an important anti-bacterial and healing agent, and its degradation products. These products were prepared by thermal decomposition of curcumin (DC) at a temperature of 180 °C (DC 180) or of 300 °C (DC 300). The main thermal decomposition products were tumerone, vanillin, and feruloylmethane. Curcumin and its degradation products were loaded into the bacterial nanocellulose by an autoclaving process. The increased temperature during autoclaving enhanced the solubility and the penetration of the agents into the nanocellulose. The aim of this study was to investigate the cytotoxicity and the antimicrobial activity of pure curcumin, its degradation products, and finally of bacterial nanocellulose loaded with these agents. In vitro tests performed on human dermal fibroblasts revealed that the degradation products of curcumin, i.e., DC 180 and DC 300, were more cytotoxic than pure curcumin. However, if DC 300 was loaded into nanocellulose, the cytotoxic effect was not as strong as in the case of DC 300 powder added into the culture medium. DC 300 was found to be the least soluble product in water, which probably resulted in the poor loading of this agent into the nanocellulose. Nanocellulose loaded with pure curcumin or DC 180 exhibited more antibacterial activity than pristine nanocellulose.
Keywords: curcumin thermal degradation; dermal fibroblasts; curcumin; bacterial nanocellulose